Unions, wages and employment in Finland - Timo Tyrväinen (Bank of Finland, 1989)
Reduced form wage and employment equations stemming from a bargaining framework are estimated with two-step method proposed by Engle and Granger (1987). Quarterly data for manufacturing and aggregate private sector is used. Step response functions due to various shocks were calculated by dynamic simulation. Adjustment was rather fast in general. If the actual real wage-employment combination is considered as inappropriate, it is not due to labour market rigidities. It rather implies that the equilibrium is inappropriate. Out-sample short-run forecasts were also simulated. In addition to standard variables several tax variables as also a proxy for union power was included. The positive effect found for union strength on both wages and employment in manufacturing industry is not evaluated as an evidence for efficient contract model.
URN:NBN:fi:bof-201908051343
Keywords: 330